Adjustment Costs and Incentives to Work: Evidence from a Disability Insurance Program - Arezou Zaresani (Institute of Labor Economics (IZA), 2019)
How important are adjustment costs for individuals when they face a change in work incentives induced by a policy change? I provide the first estimate of heterogeneous adjustment costs by exploiting a policy change that substantially increased work incentives. The policy change increased the exemption threshold in a disability insurance program. I document strong responses to work incentives as I observe excess mass –"bunching"– right below the exemption threshold where the marginal tax on earnings is low. A puzzling observation is that individuals continue bunching at the former threshold after the policy change. This finding suggests that they face adjustment costs when changing their labor supply. I use the amount of bunching at the new and former threshold to estimate adjustment costs that vary by individuals' ability to work. The estimated adjustment costs are higher for individuals with lower ability; varying from zero to twenty percent of their potential earnings, with an average at eight percent. The estimated elasticity of earnings respect to net-of-tax rate – accounting for heterogeneous adjustment costs – is 0.2, which is double the size of the elasticity estimated with no adjustment costs. To investigate the relative size of the adjustment costs to the work incentives induced by the policy change, I evaluate the overall effect of the policy change on the labor supply using a Difference-in-Differences design. I find that individuals who already work, work more, and those who did not work, start working. Policies designed to increase labor supply will work if the induced work incentives are large enough to offset the adjustment costs. Accounting for adjustment costs then might explain disparate findings on the effects of an increase in work incentives on labor supply in disability insurance programs. These findings have important implications for designing policies and targeting heterogeneous groups to increase labor supply in disability insurance programs.
Keywords: H53; J21; J18; 330; adjustment costs; bunching; kink; elasticity; disability insurance